Study on Effects of 1857 Revolt on Haryana and Its Adjacent Region: The Impact of British Atrocities and Sikh Involvement during the 1857 Revolt in Haryana and Its Adjacent Region (Journal of Advances and Scholarly Researches in Allied Education, 2012)
With such atrocities committed by the British on thepeople of Punjab, they deserved no sympathy, or assistance from the Sikhs. But,cis-Sutlej Sikh Rajahs, jumped on their band wagon, because they were treatybound The British did receive reinforcements from England later, and might havesurvived, but even before their arrival the tide had turned in their favor.